PENINGKATAN KEMAMPUAN MENELAAH STRUKTUR CERITA FANTASI MENGGUNAKAN METODE PETA PIKIRAN - Febriyanti, Ika (sarasvati, 2020)
The first objective of this research is to describe the ability to find the structure of fantasy stories of grade 7 A students at SMP Negeri 2 Jombang using the mind map method. The second is to describe the application of learning using the mind map method to improve the ability of grade 7 A students at SMP Negeri 2 Jombang. The research design used classroom action research. This type of research, namely qualitative and quantitative. The place of research is SMP Negeri 2 Jombang. The data in this study were the results of observations and tests of students finding the structure of fantasy stories. The data from the students' test results found that the structure of the fantasy story was analyzed quantitatively which was then described in words or sentences. The results showed that of the 30 students in the 10 groups as a whole entered at a good level. Based on this assessment, it can be seen that the class average score reaches the success criteria. The value of the ability to find the structure of a fantasy story, namely orientation, complications, and resolution in The Little Mermaid film can be seen per criteria. Based on the results of the scores, it can be concluded that most of the students have made progress in concluding all the parts in the fantasy film The Little Mermaid.